O sistema semântico de projeção e sua dispersão gramatical em português brasileiro: uma descrição sistêmico-funcional orientadapara os estudos lingüísticos da tradução - Cristiano Goncalves Araujo (2007)
This study conceives of systemic-functional linguistics as an integrating part of a model to approach the study of translation and aims at contributing to this model through a description of the semantic system of PROJECTION and its dispersal in the grammar of Brazilian Portuguese. Drawing on the work of Halliday & Matthiessen (2004) as well as on other works developed within the systemic functional theory, this study develops a description of the projection of ideas and locutions, both in relation to the quote and report modes and in relation to the speech function (whether proposal or proposition) of the projected clauses. In order to pursue the description proposed in this study, a corpus composed by texts in Brazilian Portuguese belonging to different registerial domains was compiled, amounting to about 30.000 tokens. This corpus was annotated and data was retrieved with the aid of WordSmith Tools software. Based on the collected data this study described patterns of ocurrences that allowed for the characterization of the configurational patterns of the semantic system of PROJECTION in Brazilian Portuguese. The results obtained by means of this analysis can inform other studies that adopt the systemic functional framework in order to approach translation and multilingual text production.